Збір інформації про діяльність учасників групи в соціальній мережі Facebook - Марковець, Олександр; Паздерська, Руслана (Видавництво Львівської політехніки, 2018)
These studies investigate the problem of illegal collecting information in the social network. The description of safe methods for collecting information. Opportunities for people who directly manage the data collection process.
Keywords: збір інформації; методи збору інформації; статистичні дані; соціальна мережа; адміністратор; користувач